Chronic pain following inguinal herniorrhaphy: perceptions of children and adolescents - Louise Amália de Moura; Pâmela Roberta de Oliveira; Marcelo Medeiros; Lisabelle Mariano Rossato; Natália de Carvalho Borges; Lilian Varanda Pereira (SciELO, 2021)
ABSTRACT Objective: To analyze the perceptions of children and adolescents about chronic postsurgical pain, experienced for three years after outpatient inguinal herniorrhaphy. Method: Descriptive, exploratory study, with a qualitative approach. Children and adolescents who reported chronic postsurgical pain were invited from previous quantitative research. The interviews with a semi-structured script were recorded, transcribed, and coded according to content analysis, thematic modality. Results: Twenty children and teenagers participated. They attributed different meanings to chronic persistent postsurgical pain, configuring a bad, uncomfortable, intermittent and limiting experience, which socially isolates, interferes with daily, school, and leisure activities. The report of pain was underestimated and neglected by the children's and adolescents' healthcare team, family members, teachers, and friends. Conclusion: Children and adolescents recognize postsurgical pain as persistent pain and seem to perceive that their report is underestimated and neglected by parents and teachers. Additionally, they feel responsible for the presence of pain that affects psychological and social dimensions and imposes damage and fear that leads to the return of the hernia and to death.